Dual Band Filter-Antenna with Fixed Low Band and Frequency-Agile High Band for Wireless Communications - Atallah, H. A. (Advanced Electromagnetics, 2020)
This work proposes a design of compact filter-antenna with fixed and frequency-agile bands for wireless communications and cognitive radio (CR) systems. The filter-antenna is realized by attaching a bandpass filter with an independent fixed band and a tunable band to a UWB antenna. The dual bandpass filter consists of a folded open loop resonator loaded with single varactor diode at a suitable location to achieve reconfigurability operations for the high band while the low band remains fixed at 4.5 GHz. A reconfigurable broadband frequency range of 3.2 GHz from 7.8 to 4.6 GHz is achieved for the high band by changing the capacitance of the varactor from 0.16 to 2.25 pF, respectively. A prototype of the filter-antenna is fabricated and measured at a selected capacitance of 0.6 pF to verify the simulation results. Good agreements between simulated and measured results are obtained.